Youth voluntary organization, leadership and intergroup relationship in Sabah, Malaysia: a preliminary discussion - Mohd. Sohaimi Esa; Romzi Ationg; Suraya Sintang; Abang Mohd Razif Abang Muiz; Mohd. Azri Ibrahim; Sirahim Abdullah (2020)
If the youth voluntary associations’ common goals are to be achieved, their leaders must embrace leadership ethics that are the most effective in leading and motivating people to actively execute their job. In carrying out their leadership role, it is also important to note that the leaders always required considering the role played by the factor calls intergroup relations. Accordingly, based on literature as well as documents review, this paper briefly discusses the importance of understanding the relationship between leadership ethics and intergroup relations in effort to consolidating youth development in Sabah. The paper thus shows that leadership ethics is a key determining factor in the attainment of youth voluntary common goals with consideration of intergroup relationship factor within the organization. Nevertheless, it is argued that a further study to be done for clarification on this matter.